Pengaruh Media Sosial Terhadap Kasus Bullying dan Dampaknya Terhadap Kesehatan Mental pada Siswa SMP di Kabupaten Soppeng - Nurhardianti Ibrahim; Sapriana Sapriana (Jurnal Ners, 2026)
The widespread use of social media among adolescents has significantly affected their social behavior and mental health. This study aimed to analyze the influence of social media use on bullying behavior and its impact on the mental health of junior high school students in Soppeng Regency. Using a quantitative quasi-experimental design (pretest–posttest), data were collected from 521 respondents through questionnaires, interviews, observations, and focus group discussions. Statistical analyses included descriptive tests, t-test, Chi-Square, and binary logistic regression. The results showed that 79.2% of students frequently or very frequently used social media, 35.9% had been victims of bullying, and 76.4% had acted as perpetrators. A total of 63.8% reported negative mental health impacts. The t-test revealed significant differences in mental health between students affected and unaffected by social media (p = 0.001). Regression analysis identified age, gender, and bullying experience as factors significantly influencing mental health (p < 0.05). These findings suggest that social media indirectly affects students’ mental health through bullying experiences. Therefore, school-based prevention and counseling programs are needed to strengthen adolescents’ psychological resilience